The Twilight Zone: OTC Regulatory Regimes and Market Quality - Brüggemann, Ulf; Kaul, Aditya; Leuz, Christian; Werner, Ingrid M. (Review of Financial Studies, 2018)
Studying a comprehensive sample of stocks from the U.S. OTC market, we show that this market is a large and diverse trading environment with a rich set of regulatory and disclosure regimes, comprising venue rules and state laws beyond SEC regulation. We exploit this institutional richness to show that OTC firms subject to stricter regulatory regimes and disclosure requirements have higher market quality (higher liquidity and lower crash risk). Our analysis points to an important trade-off in regulating the OTC market and protecting investors: lowering regulatory requirements reduces the compliance burden for smaller firms, but it also reduces market quality.